ZVS Soft-switching Push-pull DC/DC Converter - 袁义生; 熊晶; 艾东兵 (Kongzhi Yu Xinxi Jishu)
For the application of push-pull DC-DC converter, two soft-switching circuits with the LLC series resonant and LCL parallel resonant on sub-side of the transformer are investigated. In-depth analysis and discussion is made on the working stages of these two circuits and their principles of soft switching, the working features between the two circuits are compared, and the actual circuits are further assembled and tested. The results show that two circuits can realize the soft-switching of power transistors, and the correctness and validity are proved.